تطبيق تعليم مهارة الكلام في المدرسة المتوسطة منبع الإحسان - Arif Widodo; Hana Chebaiki; Arif Satria (Kilmatuna: Journal Of Arabic Education, 2021)
The primary goal of teaching non-native speakers of Arabic in general is for students to acquire a set of basic linguistic skill in speaking Arabic. This skill is considered one of the basic skills until the student seeks to master it, and it is considered an essential expressive production skill. Today, the urgent need for this skill has become in order to achieve verbal communication, and its importance has increased through oral communication among people. It is essential when teaching this skill to pay attention to the verbal aspect and the method used in it. The method used by the researcher in this research is the descriptive method and the method of collecting data by observing with participation, in-depth interview and the document. This research is a field research type where the researcher used to take information and data related to teaching skill of speech. The data was analyzed using the content analysis model. As a result of what the researcher showed about teaching the skill of speaking in middle school, it was found that its teaching adheres to the dialogue entrance and supportive activities to dialogue, the Arabic song and the experience of presenting the question and answer by means of a microphone to raise the students' voice and to bring their results so that their minds are strong. In this way, each student is interested in his studies, and his participation in the teaching and learning process in the classroom, as well as his activity in the classroom, has increased. As for their attendance, this indicates that their degree has reached 95%.